Prevalence and antimicrobial susceptibility patterns of Neisseria gonorrhea among the symptomatic patients attending outpatient department in Lyatonde district hospital southwestern Uganda - Peace, Nakiwala; Elliot, Ahabwe; Lawrence, Nseera; Felix, Twiine; Apecu, Richard Onyuthi (International Journal of Scientific Reports, 2019)
Background: Neisseria gonorrhea is one of the neglected diseases of public health importance causing symptomatic, suppurative discharge in males and being asymptomatic in females. This cross-sectional study was aimed at determining the prevalence and susceptibility pattern of Neisseria gonorrhea to the commonly used antibiotics among symptomatic patients attending outpatient department in Lyatonde district hospital. Methods: Urethral and endocervical swabs were collected by the attending medical laboratory technologists. The presence of gonorrhea was confirmed by culture, Gram staining and biochemical tests. Antimicrobial sensitivity test was performed using the disc diffusion method and the result was interpreted using the National Committee for Clinical Laboratory Standards guidelines. Results: Overall prevalence of N. gonorrhea was 4.9% with high prevalence rates of 7.7% among the young age group of 15-25 years. Low level of antimicrobial susceptibility to cefuroxime (50%) followed by erythromycin and gentamycin both at 25% was observed. An alarming resistance to ceftriaxone and ciprofloxacin at 100% followed by penicillin 75% was exhibited by the colonies. Conclusions: The high resistant rate to ceftriaxone and ciprofloxacin obviates their use as the first line of syndromic treatment of gonorrhea in Southwestern Uganda. The use of laboratory culture for diagnosis and management of N. gonorrhea, especially with cefuroxime therapy is highly recommended.
Keywords: Antibiotic susceptibility; Neisseria gonorrhea; Prevalence; Uganda